The Influence of Binary Opposition and Stylistic Devices on Reader Interpretation of Quranic Themes - Kazmi, Sarah Syed (Pakistan Languages and Humanities Review, 2025)
This study examines the structural and stylistic aspects of the Quranic text with a special focus on binaries and dichotomies with the aim of explaining how these binaries are contextually employed and supported rhetorically in selected verses. Binary forms are a distinct characteristic of Quranic discourse which direct the thematic elements of divine justice, divine guidance and dialectic of faith versus unbelief. The structuralist theory presents a powerful analytical model, inquiring the functional interplay of these oppositions. A qualitative and interpretive approach will be used in the current study to analyse specific verses with a view to identifying the binary oppositions that are predominant and the rhetorical devices that perpetuate them. The results indicate that future studies ought to expand their horizons to include larger narrative units to have a more comprehensive mapping of the Quranic dichotomies, conduct comparative studies to understand how these rhetorical units work to shape the meaning for readers, and apply cognitive and reader-response models to gain a deeper insight into the effect of these rhetorical units.